784 Naturalistic Measurement of Sleep/Wake Disturbance in Adults Receiving Methadone Treatment for Opioid Use Disorder. (3rd May 2021) - Skeiky, Lillian; Hansen, Devon; Layton, Matthew; Quock, Raymond; Van Dongen, Hans; Wilson, Marian
Abstract: Introduction: Individuals with opioid use disorder (OUD) report significant sleep/wake disturbance, which continues even after stabilization on medication-assisted treatment (MAT). However, the nature of sleep/wake disturbance in this population has not been well documented objectively. Here we analyze naturalistic wrist actigraphy recordings in individuals with OUD receiving methadone-based MAT. Methods: Seven adults undergoing methadone treatment for OUD (ages 26–50; 4 women) wore a wrist actigraph (Actiwatch-2, Philips Respironics) continuously for 7 days. They were asked to adhere to their normal sleep schedule in order to obtain naturalistic observations. Reference data were collected in a separate study of healthy controls, in which 14 hospital nurses (ages 20–60; 13 women) wore a wrist actigraph continuously for 7 days. In this reference group, 7 participants had a day shift schedule (07:00–19:00) and 7 had a night shift schedule (19:00–07:00), with six 12h shifts in a 2-week period. Actigraphic data were collected in 1min epochs, and the sleep/wake status for each epoch was estimated using Actiware 6.0.9 (Philips Respironics). The estimated sleep/wake patterns were subjected to cosinor analysis to assess 24h rhythmicity and analysis of the distribution of inactive periods to assess sleep continuity. Results: For the reference group, nurses working day shifts displayed strong 24h rhythmicity, whereas nurses working night shifts showed blunted 24h rhythmicity (F[1, 12]=66.11, p<0.001). However, both day and night nurses exhibited high sleep continuity (KS test, p=0.82). By contrast, for the group with OUD receiving methadone, the strength of 24h rhythmicity was reduced to between that of the day and night shift nurses in the reference group, indicating weak regularity of sleep/wake patterns (F[2, 18]=33.79, p<0.001). Furthermore, individuals with OUD receiving methadone experienced low sleep continuity compared to the reference group (KS test, p=0.030). Conclusion: These naturalistic observations confirm the presence of sleep/wake disturbance, resulting from both irregular sleep/wake patterns and low sleep continuity, in individuals receiving methadone-based MAT for OUD. Sleep/wake disturbance may interfere with the ability to achieve OUD recovery goals, and comparing sleep disturbance in MAT populations to reference data highlights the need to consider sleep in these populations as a clinical priority. Support (if any): State of Washington Initiative Measure No. 171